Analysis The Effect of Problem Based Approaches and Media Experiment on Learning Interest and Critical Thinking Using Structural Equation Modeling - Devita Sari; Singgih Bektiarso; Albertus Djoko Lesmono (Berkala Ilmiah Pendidikan Fisika, 2022)
The 21st-century national education paradigm requires students to have new abilities, such as critical thinking ability. However, students' critical thinking skills are still low. Likewise, interest in studying physics is still low. Physics is often considered a difficult subject, discouraging interest in studying physics. This study aims to examine the effect of a problem-based approach and experimental media on the interest in learning physics and the critical thinking skills of class XI high school students using SEM analysis. This research was conducted at senior high school on 4 Jember. The research data were collected using a questionnaire tested for validity and reliability. Furthermore, the data were analyzed using SEM analysis, developing a theoretical model, developing a flow chart, and evaluating the goodness of fit criteria. The results obtained, the problem-based approach has a significant effect on the interest in learning physics, the media for the experimental tool has a significant effect on the interest in learning physics, the problem-based approach has a significant effect on students' critical thinking skills, and the media for the experimental tool has a significant effect on the critical thinking skills of grade XI high school students. In addition, it was found that the interest in learning physics was able to mediate the effect of a problem-based approach on critical thinking skills and the influence of experimental media on critical thinking skills. So we can conclude that each dependent variable and the independent variable influence each other significantly.